Decidual stromal cell-derived IL-33 contributes to Th2 bias and inhibits decidual NK cell cytotoxicity through NF-κB signaling in human early pregnancy. (June 2015) - Hu, Wen-Ting; Huang, Li-Li; Li, Ming-Qing; Jin, Li-Ping; Li, Da-Jin; Zhu, Xiao-Yong
Highlights: The expression of IL-33 receptor (referred to as ST2) on decidual NKs is higher than on peripheral NKs. DSC-derived IL-33 inhibits the cytotoxic activity of decidual NKs. DSC-derived IL-33 brings out Th2 bias by modulating the secretion of cytokines by decidual NKs. DSC-derived IL-33 decreases activating receptor expression while increasing inhibitory receptor expression on decidual NKs. IL-33 induces cytokine production and phenotypic changes of decidual NKs through the NF-κB signaling pathway. Abstract: Decidual stromal cells (DSCs) are an important component of decidual tissues where they are in strict proximity with immune cells. Although previous research has indicated that DSCs participate in the regulation of immune cells during pregnancy, the crosstalk between DSCs and decidual NK cells (dNKs) has not been fully elucidated. The aim of this study was to ascertain the effect of DSC-derived IL-33 on dNK function and explore the underlying mechanism. Flow cytometry showed a considerable increase in ST2 expression on dNKs compared with peripheral NKs (pNKs). Subsequent research found that perforin production, granzyme A production, and the cytolytic activity of dNKs were impaired by DSC media. Furthermore, the addition of DSC media induced an increase in Th2 cytokine production (IL-4, IL-13, and IL-10) with a concomitant decrease in Th1 cytokine expression (TNF-α) of dNKs. However, IFN-γ, another member of the Th1 cytokine family that is thought to be necessary during early gestation increased after IL-33 stimulation. DSC media sharply inhibited the expression of major activating receptors (NKp30, NKG2D) while up-regulating the levels of inhibitory receptor (KIR2DL1) on dNKs. The biological effect of DSC media on dNKs was abrogated by the administration of sST2. Moreover, Western blot analysis suggested that the NF-κB pathway was involved in the IL-33-induced changes in the phenotype and function of dNKs, which was further confirmed by pharmacological inhibition with the NF-κB inhibitor BAY 11-7082. Our results suggest that the crosstalk between DSCs and dNKs might play a crucial role in maintaining successful pregnancy.